STUDY OF TEACHING METHOD AS A FACTOR OF SOCIAL PARTICIPATION AND DEVELOPMENT OF CRITICAL THINKING AMONG STUDENTS - TEACHERS OF FARHANGIAN UNIVERSITY (ARTICLE: TEACHING METHOD AND CRITICAL THINKING) - Ronaghi, Marzieh; Hashemianfar, Seyed Ali; Haghighatian, Mansour (International Journal of Psychosocial Rehabilitation, 2020)
The present study was conducted to investigate the effect of teaching method on the growth of critical thinking. And it aims to highlight the role of educational centers (such as the University of Cultural Sciences) in this growth process. The research hypotheses seek to explain the relationship between communicative activities and free participation without exercise of domination, the relationship between teacher teaching practices in classrooms and the growth of critical thinking among teachers of Isfahan Farhangian University as well as the relationship between gender and field of study in the spirit of participation The students of Isfahan Farhangian University were among the students. The statistical population is the students of Farhangian University a stratified random sampling method has been developed based on the gender and field of study (given that the list of all students had all the classes) and a sample of 331 were selected. The information was compiled by a researcher- made questionnaire and based on the standard Rickets critical thinking Questionnaire. Data were analyzed using SPSS and IMOS software. The results of the research indicate the hypothesis and the relationship between the research variables.